Stress-triggered hematopoietic stem cell proliferation relies on PrimPol-mediated repriming - Jacobs, Kurt; Doerdelmann, Cyril; Krietsch, Jana; González-Acosta, Daniel; Mathis, Nicolas; Kushinsky, Saul; Guarino, Estrella; Gómez-Escolar, Carmen; Martinez, Dolores; Schmid, Jonas A; Leary, Peter J; Freire, Raimundo; et al. (Molecular cell, 2022)
Stem cell division is linked to tumorigenesis by yet-elusive mechanisms. The hematopoietic system reacts to stress by triggering hematopoietic stem and progenitor cell (HSPC) proliferation, which can be accompanied by chromosomal breakage in activated hematopoietic stem cells (HSCs). However, whether these lesions persist in their downstream progeny and induce a canonical DNA damage response (DDR) remains unclear. Inducing HSPC proliferation by simulated viral infection, we report that the associated DNA damage is restricted to HSCs and that proliferating HSCs rewire their DDR upon endogenous and clastogen-induced damage. Combining transcriptomics, single-cell and single-molecule assays on murine bone marrow cells, we found accelerated fork progression in stimulated HSPCs, reflecting engagement of PrimPol-dependent repriming, at the expense of replication fork reversal. Ultimately, competitive bone marrow transplantation revealed the requirement of PrimPol for efficient HSC amplification and bone marrow reconstitution. Hence, fine-tuning replication fork plasticity is essential to support stem cell functionality upon proliferation stimuli.